A counter-mine that explodes silently: Romano and Schmitt on the unity of the legal order. Issue 2 (30th August 2018) - Salvatore, Andrea
ABSTRACT: This contribution is intended to provide an answer to a controversial question: Why does Carl Schmitt – perhaps the firmest advocate of the state unity – not only mention and praise Santi Romano's book on the legal order – a work that can be rightfully considered an uncompromising defence of legal pluralism – but even list him among his inspirers? While a given (and essentially flawed) interpretation of Romano's institutional model, like that provided by Schmitt, actually makes his concrete-order thinking better suited to cope with the legal pluralism of modern social theory (and this is a possible answer to the opening question), it ultimately reveals the serious deficiencies of what can be defined as Schmitt's institutional decisionism. Contrary to what Schmitt believes, indeed, Romano's social ontology decisively contributes to demonstrate how the argument Schmitt uses in his general attack on social pluralism can also be re-deployed in its defence. Yet, Schmitt's reappraisal of Romano's concept of institution, questionable as it may be, addresses and tackles a crucial issue – probably, the crucial issue of both the entire book and his legal institutionalism as a whole – that Romano himself appears to be unable to solve and that still remains an open and challenging question for most social theorists.